Acute Severe Hepatotoxicity Associated with Clomipramine - Atmaca, Murad (Kure Iletisim Grubu A S, 2011)
Miss Y. presented with complaints of irritability, depressed mood, avolition, anhedonia, markedly decreased appetite and around 10 kg weight loss within two months, amenorrhea, dysmorphophobia, and psychomotor retardation. The psychiatric evaluation revealed major depressive episode. She was given a prescription for 25 mg/day of clomipramine for her depression, and also cognitive behavioral therapy was started. Her level of aspartate aminotransferase was 212 IU/liter, and her alanine aminotransferase level was 474 IU/liter. Therefore, clomipramine was stopped urgently. After one month, the enzymes returned to normal values. Physicians should be alert to the possibility that clomipramine can cause acute hepatotoxicity and consider early discontinuation of an antidepressant if the condition is suspected.
Klomipramine ba?lı akut ve ciddi hepatotoksisite
Keywords: Clomipramine; hepatotoxicity; aspartate